PENGGUNAAN MEDIA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP - Sari Martiningsih (EDU-KATA, 2019)
Target of this research is to describe objectively about: (1) the kinds of Indonesian learning media, (2) the activities use media in learning of Indonesian language, and (3) the achievement of the students of SMP Negeri 3 Baureno referring to the usage of media in learning Indonesian language.To reach the target above, this research use qualitative approach. Source of data in this research is kinds of learning media used by Indonesian teachers, the teaching learning activities that use the learning media, and the students’ achievement posed at with daily test. The data collected through observation, interview, and documentation.Based on the data analysis which is described descriptive qualitative obtained the following conclusions (1) the kinds of learning media used by the Indonesian teachers in the form of conventional media, (2) the activities that use the learning media applied by the Indonesia teachers depend on the creativity of the teacher to modify the media so that the conventional media have new value because supple in its use, and (3) the achievement of students grade VII of SMP Negeri 3 Baureno referring to the usage of media in learning Indonesian language very gratifying, both aspect of language skills and aspect of language art.